Konstitusionalitas Poligami Dalam Perspektif Hermeneutika Hukum Islam di Indonesia - Eka N.A.M Sihombing; Cynthia Hadita Hadita (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
The polemic of polygamy that is still being contested in Indonesia needs to be studied from the perspective of hermeneutics of Islamic law, its constitutionality, such as how Pancasila guarantees the practice of polygamy, and also in laws and regulations whose substance also regulates polygamy. The research method used in this study is a normative juridical method with a doctrinal approach. The purpose of this study is to determine the constitutionality of polygamy when examined from the hermeneutic perspective of Islamic law in Indonesia. The results showed that the First Principle of Pancasila, Article 29 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, the Marriage Law and its implementing regulations, as well as the various views of the schools allow the practice of polygamy in Indonesia.